RESIMAFRO REPORTING SYSTEM TECHNOLOGY: AN INTEGRATED MODEL FOR RESULTS-BASED MANAGEMENT AND ORGANIZATIONAL ACCOUNTABILITY - Nurul Azni Agustin; ARIBOWO ARIBOWO; Tuti Kartika (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2026)
This study aims to develop the RESIMAFRO Reporting System Technology (Results Based Management in Organizational Information Systems) at Yayasan Amal Produktif Indonesia, Bandung. The study was motivated by reporting practices that remained focused on administrative and financial aspects, lacked systematic documentation of program outputs, outcomes, and impacts, and were not integrated into the organizational information system. A qualitative method with a Participatory Action Research (PAR) approach based on the Kemmis and McTaggart model was employed, involving foundation managers, program implementers, social workers, and relevant stakeholders. The research stages included reflection on the existing system, needs assessment, system design, implementation, evaluation, and refinement of the final design. The findings indicate that RESIMAFRO integrates results based reporting, monitoring, and evaluation through input, output, outcome, impact, performance indicators, and information dashboards that support organizational. The system improves program documentation, transparency, accountability, data accessibility, and the utilization of information for continuous program improvement. This study produces a results based reporting system design integrated with an organizational information system that can serve as a model for strengthening governance in humanitarian service organizations.